G75(P) Use of skeletal surveys in suspected non accidental injury within the United Kingdom. (24th May 2017) - Pandya, A; Kisat, H
Abstract : Aim: The RCPCH standards state a skeletal survey is the initial imaging method for evaluation of children where non-accidental injury is suspected with clear guidelines as to when surveys should be performed. Skeletal surveys require substantial resources to be performed and reported. In the current financial climate we wanted to evaluate the clinical use and practice of skeletal surveys in suspected non-accidental injury across the country. Methods: An online anonymous survey (survey monkey) was cascaded to the college tutors via RCPCH. Results were collected and analysed. Results: We received 39 responses out of 250 college tutors. 95% of tutors stated they routinely request skeletal surveys in the <1 year group, 50% in the <2 group and 10% in >2 years. 43% of tutors report skeletal surveys are performed within 24 hours and 54% are performed between 24–48 hours from request. 94% stated they had a weekday only reporting service.39% of tutors responded that average skeletal survey reporting occurred within 24 hours, 47% within 24–48 hours and 13% taking longer than 48 hours for a formal report to be issued. 97% of tutors reported that skeletal survey reporting is done locally. Of this 97%, 17% of them also outsource reporting for a second opinion. 83% of respondents stated that children would be admitted until a formal report was issued. Conclusion: We are requesting less skeletal surveys in the <2 age group than college guidelines would recommend. The vast majority of responses show that skeletal surveys are performed within a 48 hours window from requesting. The majority of reporting is performed locally however around 17% also outsource their reporting for second opinions which increases financial burden. The majority of respondents report that children would be admitted until a formal report was issued. Given that most college tutors state a weekday only reporting service children can be admitted overnight, creating a substantial demand on hospital beds. Further education should be provided to paediatric teams on when skeletal surveys are indicated and the financial and practical implications this has on the NHS. A limitation of this project is the low response rate, however reminder emails will be sent out to address this issue and results will be reanalysed.